2012
DOI: 10.1152/ajpcell.00181.2011
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol attenuates high glucose-induced endothelial nitrotyrosine: role for neuronal nitric oxide synthase

Abstract: Chakrabarti S, Cheung CC, Davidge ST. Estradiol attenuates high glucose-induced endothelial nitrotyrosine: role for neuronal nitric oxide synthase. Am J Physiol Cell Physiol 302: C666 -C675, 2012. First published November 30, 2011 doi:10.1152/ajpcell.00181.2011.-Hyperglycemia in diabetes causes increased oxidative stress in the vascular endothelium with generation of free radicals such as superoxide. Peroxynitrite, a highly reactive species generated from superoxide and nitric oxide (NO), induces proinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This higher number of death cells under HG conditions seems to be caused by an increase in NO, because addition of the NOS inhibitor L-NAME under HG conditions decreased the amount of death cells. The involvement of NO in glucose toxicity has been described previously [34], [35], [36]. Another indication of the involvement of NO in endothelial cell death was found when HUVECs were incubated with the peroxynitrite generator SIN-1.…”
Section: Discussionmentioning
confidence: 60%
“…This higher number of death cells under HG conditions seems to be caused by an increase in NO, because addition of the NOS inhibitor L-NAME under HG conditions decreased the amount of death cells. The involvement of NO in glucose toxicity has been described previously [34], [35], [36]. Another indication of the involvement of NO in endothelial cell death was found when HUVECs were incubated with the peroxynitrite generator SIN-1.…”
Section: Discussionmentioning
confidence: 60%
“…Brain cell cultures of mice exposed to 17β-estradiol significantly reduced 3-NY levels regardless of whether or not they have been exposed to superoxide [ 64 ]. Estrogen can directly inhibit nitric oxide synthase (NOS) activity, thereby reducing peroxynitrite and subsequently 3-NY generation [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Premenopausal women are relatively protected against cardiovascular diseases (CVDs) compared to age-matched men, possibly because of higher circulating levels of female sex hormones (e.g., estrogen) which are believed to play a protective role by their favorable effect on vascular structure, function, and cell signaling [1315]. However, it has been suggested that some of the estrogen effects on the endothelium may be modified or attenuated in various pathological states characterized by the increased level of oxidative stress [16, 17], which is also present in DM and has been shown to play a pivotal role in the development of diabetes complications [47]. It has still not been elucidated how the vasculoprotective role of estrogens is affected in women with DM who have a high incidence of CVDs.…”
Section: Introductionmentioning
confidence: 99%